?UTILIZATION OF AGRICULTURE WASTES. PART 1.PRODUCTION OF FUNGAL PROTEIN FROM RICE AND WHEAT STRAWS (Biological Sciences - PJSIR, 2000)
Agricultural waste of rice and wheat straws were studied for the production of protein and biomass. As these wastes have low protein contents an attempt is made to increase the protein and biomass content 01"these wastes so as to produce a better product for consumption as food. The studies were conducted using various media and various incubation periods. Some inorganic salts and molasses were added to improve the cultivation of fungi. Aspergillus oryzae produced the best results due to its rapid growth which minimized the chance of contamination. Seven days incubation gave the most favourable results in both the agricultural wastes. The maximum production of biomass' (33.33%) with a protein value of 20% was obtained with 450 g of rice straw in media no. 2 whereas 400 g of wheat straw on 6 litres of medium produced the best results with 20% biomass and a protein value of 20%.